2010
DOI: 10.5210/fm.v15i3.2841
|View full text |Cite
|
Sign up to set email alerts
|

Individual focus and knowledge contribution

Abstract: Before contributing new knowledge, individuals must attain requisite background knowledge or skills through schooling, training, practice, and experience. Given limited time, individuals often choose either to focus on few areas, where they build deep expertise, or to delve less deeply and distribute their attention and efforts across several areas. In this paper we measure the relationship between the narrowness of focus and the quality of contribution across a range of both traditional and recent knowledge s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Adamic et al (2010) found a significant correlation between focus and quality of individual contribution across a range of traditional and modern knowledge sharing media including Wikipedia: narrower individual contribution domains resulted in higher and more consistent quality. In addition, Anthony et al (2009) gue h " eg s e e p c p n s, mo v e y epu on n comm men o he Wikipedia commun y, m ke m ny con u ons w h h gh el l y.…”
Section: Individual Aspectsmentioning
confidence: 94%
“…Adamic et al (2010) found a significant correlation between focus and quality of individual contribution across a range of traditional and modern knowledge sharing media including Wikipedia: narrower individual contribution domains resulted in higher and more consistent quality. In addition, Anthony et al (2009) gue h " eg s e e p c p n s, mo v e y epu on n comm men o he Wikipedia commun y, m ke m ny con u ons w h h gh el l y.…”
Section: Individual Aspectsmentioning
confidence: 94%
“…However, treating skills as interchangeable removes some of the richness of human capital: workers’ skills are clearly heterogeneous and multidimensional as are the skills required for jobs. A considerable body of literature shows the importance of skill diversity, specialization, and recombination in problem-solving and knowledge generation ( 2 8 ). This plus continued growth in knowledge-based industry ( 9 ) have generated interest in more nuanced measures of human capital ( 10 19 ).…”
mentioning
confidence: 99%
“…Significant correlation is found between focus and quality of individual contribution across a range of traditional and modern knowledge‐sharing media including Wikipedia; the narrower the individual contribution domain is, the higher quality and even quantity it would have (Adamic et al., ).…”
Section: Quality Of Contentmentioning
confidence: 99%